- Meninjau Keuntungan dan Tantangan Indonesia selaku Ketua ASEAN Summit 2023 atas Kerja Sama IMT-GT dalam Kaitan BRI (Belt and Road Initiative) - Yolin, Theresia Kariani; Rantepadang, Fenny Novita (Jurnal Sentris, 2023)
IMT and BRI is international collaboration that aim to improve the economic growth and connectivity. The background of this study to review opportunity and challenge Indonesia as a corporation country with IMT-GT and BRI, also its position as ASEAN Summit Leader 2023. Globalization crate corporation and dependency between countries increasingly unavoidable, so this openness give the opportunity and challenge to country and organization. Establish the BRI Program make a challenge to ASEAN direct or according IMT-GT corporation as a collaboration three country of ASEAN. China as one economic hegemony of the world now according BRI program give the impact to capacity and connectivity area. The purpose of this study to review impact BRI police to IMT-GT corporation which have chance to improve accessibility area to economic growth according goal of IMT-GT. But BRI position also can make the challenge to IMT-GT like dependency to China as also possible make big impact to quality IMT-GT corporation. This study using qualitative analysis method with secondary data. The study shows BRI possible give impact to ASEAN country relation, dependency to China, and capacity connectivity ASEAN area.   Keywords: IMT-GT; BRI; Efektivitas Kawasan; Connectivity